Inhibititory effects of Datura stramonium L. plant extracts on germination and growth of wheat and barley seeds. (Albayan Scientific Journal, 2023)
Datura herbs toxic are spread close to wheat and barley crops, especially in Al- Jabal Al-Akhdar region, and Because of importance of these agricultural crops in Libya.. This study aims to know inhibitory effects of aqueous extracts of Datura stramonium L. leaves, seeds and roots at a concentration of (20, 40, 80%) on germination of wheat and barley seeds. The results showed that there were highly significant differences in germination percentage reduction and an increase in average germination time between aqueous extracts and concentrations compared with control, where extracts of leaves and roots excelled in recording the largest inhibiting ratios compared to seed extract, the results showed also that all tested concentrations were significantly reduced from root and shoot system lengths, except the 20% concentration of seed extract, which had no apparent effect on reduction of shoot system of both plants, it was also noted that wheat is more resistant to aqueous extracts than barley, and was a concentration 80% is most toxic in inhibiting studied traits.
Keywords: Datura stramonium L; Inhibititory effects; Wheat & barley